Storyworlds: the bears and the honey - Gaines, Keith; Williams, Jenny (Heinemann UK, 2009)
This fantastic range of fiction for Shared, Guided and Independent reading gives you stories your children will love to read over and over again. Gaelic and Scottish teaching support also accompanies this reading series.